¿Primos o hermanos? Nacionalismo, integralismo y humanismo cristiano en la Argentina de los años sesenta - José A. Zanca (Amnis)
Studies on the history of the Catholicism in Argentina in the 20th century claim there were very few changes between the first postwar period and the1980s. Many of these studies state that, in spite of the change of discourse, there was an intransigent matrix that openly rejected modernity. In the 1930’s, that rejection was expressed by the «myth of the Catholic nation». Furthermore, these interpretations consider Council Vatican II as a «rearrangement» rather than as a radical change. This article tries to debate these ideas, through the analysis of the tradition of Christian Humanism. Our goal is to link the changes within Catholicism with the process of social secularization. In this sense, this work considers Christian humanism as «an internal agent of secularization», as its practices and discourse allowed the decrease of the importance of authority in the religious culture.